DEMOLITION: TANTANGAN PELESTARIAN ARSITEKTUR KAWASAN KESAWAN MEDAN - Dwi Lindarto Hadinugroho (Jurnal Koridor, 2018)
Today's modern development puts the area of heritage in the classic dilemma in the management area of heritage between conservation and development of modernity. This study aims to examine how the form of demolition that occurs in architecture at the Kesawan District. Using a qualitative descriptive method through interpretative criticism evocative then this study identifying the model of demolition objects architectural heritage in the Kesawan District. This study revealed and indicating the existence of a variant form of demolition model issues are amputation, inactivity, redesign, masking/facelift, visual blurring and architecture sprawl. A number of heritage objects originality 17.14% indicates the level of concern occurred in the demolition of Kesawan District. This study can be used as a toolo of preservation action and evaluation for all stakeholders and the Medan City Government.